Redosing of Fluorescein Sodium Improves Image Interpretation During Intraoperative Ex Vivo Confocal Laser Endomicroscopy of Brain Tumors - Abramov, Irakliy; Dru, Alexander B.; Belykh, Evgenii; Park, Marian T.; Bardonova, Liudmila; Preul, Mark C. (Frontiers in Oncology, 2021)
Background: Fluorescein sodium (FNa) is a fluorescence agent used with a wide-field operating microscope for intraoperative guidance and with confocal laser endomicroscopy (CLE) to evaluate brain tissue. Susceptibility of FNa to degradation over time may affect CLE image quality during prolonged surgeries. This study describes improved characteristics of CLE images after intraoperative redosing with FNa. Methods: A retrospective analysis was performed using CLE images obtained ex vivo from samples obtained during tumor resections with FNa-based fluorescence guidance with a wide-field operating microscope. The comparison groups included CLE images acquired after FNa redosing (Redose Imaging Group), images from the same patients acquired after the initial FNa dose (Initial-Dose Imaging Group), and images from patients in whom redosing was not used (Single-Dose Imaging Group). A detailed assessment of image quality and interpretation regarding different FNa dosage and timing of imaging after FNa administration was conducted for all comparison groups. Results: The brightest and most contrasting images were observed in the redose group compared to the initial-dose and single-dose groups (P<0.001). The decay of FNa signal negatively correlated with brightness (rho = -0.52, P<0.001) and contrast (rho = -0.57, P<0.001). Different doses of FNa did not significantly affect the brightness (P=0.15) or contrast (P=0.09) in CLE images. As the mean timing of imaging increased, the percentage of accurately diagnosed images decreased (P=0.03). Conclusions: The decay of the FNa signal is directly associated with image brightness and contrast. The qualitative interpretation scores of images were highest for the FNa redose group. Redosing with FNa to improve the utility of CLE imaging should be considered a safe and beneficial strategy during prolonged surgeries.